A Flow-Based Explanation for Return Predictability - Lou, Dong (Review of Financial Studies, 2012)
This paper proposes and tests an investment-flow based explanation for three empirical findings on return predictability -the persistence of mutual fund performance, the "smart money" effect, and stock price momentum. Since mutual fund managers generally scale up or down their existing positions in response to investment flows, and the portfolios of funds receiving capital generally differ from those that lose capital, investment flows to mutual funds can cause significant demand shocks in individual stocks. Moreover, given that mutual fund flows are largely predictable from past fund performance and past flows, this paper further establishes that flow-induced price pressure is predictable. Finally, this paper shows that such flow-based return predictability can fully account for mutual fund performance persistence and the "smart money" effect, and can partially explain stock price momentum.